Body mass index and food neophilia as correlates of snack portion size selection: a cross-sectional behavioral study - Aisyah Pratiwi; Anna Undarwati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examined the association between Body Mass Index (BMI) and Food Neophilia with snack portion selection size among undergraduate students. A quantitative cross-sectional design with a behavioral measurement approach was applied. An a priori power analysis using G*Power indicated a minimum sample size of 107 participants (power = 0.95, α = 0.05), and a total of 115 students from the Faculty of Education and Psychology, Universitas Negeri Semarang, participated in the study. snack portion size selection was assessed using a real-food buffet consisting of four snack items, while Food Neophilia was measured using the Variety Seeking Tendency (VARSEEK) Scale. BMI was calculated based on participants weight and height measurements obtained using provided weighing scales and measuring tapes. Data were analyzed using multiple linear regression after all statistical assumptions were met. The results showed that Food Neophilia was negatively associated with portion size (β = -0.0776; 95% CI [-0.1234, -0.0317], p < 0.001), indicating that individuals with higher levels of Food Neophilia tended to select smaller snack portions. Although BMI showed a positive association with portion size (β = 0.0451; 95% CI [-0.0016, 0.0917], p = 0.058), the relationship became weaker after controlling for gender. In addition, male participants tended to select larger snack portions than female participants (β = 0.9516; 95% CI [0.4778, 1.4252], p < 0.001). The model explained 26.4% of the variance in portion size (R² = 0.264). These findings suggest that snack portion size selection may be influenced by a combination of psychological, demographic, and physiological factors, although the association between BMI and portion size became weaker after controlling for gender. The study highlights the importance of considering food-related personality traits and demographic characteristics in understanding eating behavior and supports further research involving more diverse populations.